Analysis of Indonesia's Automotive Component Export by Country of Destination Using Multivariate Analysis - Dedy Sugiarto; Triwulandari S. Dewayana; Dorina Hetharia; Tiena Gustina Amran (Universitas Muhammadiyah Surakarta, 2015)
The aim of this paper was to present an overview of Indonesia's automotive component export by the country of destination. The data were taken from the Statistics Indonesia (Badan Pusat Statistik/BPS) of 2014, particularly the code of HS8708. Descriptive statistics, cluster analysis and principal component analysis were used in the analysis. The results showed that histogram of total export value indicated that the curve was skewed to the right which means there were some extreme values on the right. The largest export value, subsequently, came from Thailand, Japan, and Malaysia. Based on dendogram of the cluster analysis, there were five clusters of country of destination. Meanwhile the countries of destination include Thailand, Japan, Malaysia, Brazil, Mexico, and others. Biplot principal component analysis identified the diverse characteristics of export destination countries among clusters. Gear boxes, clutches, and chasis frames were mostly demanded by Thailand; most of road wheels and part of radiators were exported to Japan; numbers of fuel tanks were sent to Malaysia; drive axles were mostly exported to the cluster of China, United Kingdom, and Philippines; while high demand of radiator spare-parts were obtained from United States.